Treatment of superficial fungal infections - recommendations of experts of Mycological Section of Polish Dermatological Society - Romuald Maleszka; Zygmunt Adamski; Jacek Szepietowski; Eugeniusz Baran (Termedia Publishing House, 2015)
Fungal infections are very commonly occurring diseases in everyday dermatological practice, and knowledge of the wide spectrum of antifungal preparations available nowadays is helpful in almost all medical disciplines. The treatment of fungal infections should be preceded with a proper diagnosis based on the patient's history, precise clinical examination and diagnostic mycological procedures. A correct diagnosis of fungal infection is possible by its confirmation with proper investigations carried out in a mycological laboratory. The main criteria of diagnosis of fungal infection justifying its therapy is isolation and identification of the fungal pathogen from the patient. In the review of the treatment of the fungal infections most commonly occurring in dermatological practice, the best known antifungals currently used in our country, whose usefulness in clinical practice has been confirmed by long-term observations, are presented. We hope that the presented treatment proposals of the most commonly occurring superficial fungal infections will be helpful in everyday medical practice.